2019
DOI: 10.1002/ente.201800889
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Metal–Organic Sulfides as Anode Materials for Lithium‐Ion Batteries at Room Temperature

Abstract: To relieve the volume effect of metal‐based anode materials for lithium‐ion batteries the size of the active material is reduced to a limit, and organic frameworks are used to provide cushioning for volume expansion. Tin‐based sulfide is designed by 1,3,5‐triazine‐2,4,6‐trithiol trisodium (TMT), and tin dichloride is synthesized at room temperature. TMT like the “solvent” of metal ions has a good electrical conductivity, which makes metal ions disperse in the organic conductive skeleton at the atomic level. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Accordingly, the flexible 3D networks of conductive polymer gel were employed to tolerate the huge volume transformation during the electrochemical reaction, thus ensured the expedite transmission and conduction path and kept the anode robust during cycling [141]. In addition, Dai et al [142] reported atomically dispersed metal sulfide anode materials were designed by the 1, 3, 5-triazine-2, 4, 6-trithiol trisodium (TMT) and Sn 2+ loading on CNT networks. TMT is similar to the ''solvent" of metal ions with good conductivity, which makes the ions uniformly dispersed in the organic framework.…”
Section: D Nanostructures Of Organic Anodesmentioning
confidence: 99%
“…Accordingly, the flexible 3D networks of conductive polymer gel were employed to tolerate the huge volume transformation during the electrochemical reaction, thus ensured the expedite transmission and conduction path and kept the anode robust during cycling [141]. In addition, Dai et al [142] reported atomically dispersed metal sulfide anode materials were designed by the 1, 3, 5-triazine-2, 4, 6-trithiol trisodium (TMT) and Sn 2+ loading on CNT networks. TMT is similar to the ''solvent" of metal ions with good conductivity, which makes the ions uniformly dispersed in the organic framework.…”
Section: D Nanostructures Of Organic Anodesmentioning
confidence: 99%